2019
DOI: 10.3390/su11195449
|View full text |Cite
|
Sign up to set email alerts
|

Implementing LEED v4 BD+C Projects in Vietnam: Contributions and Challenges for General Contractor

Abstract: Sustainable construction addresses both rising housing demand and the need to reduce energy consumption, but is not yet widespread in Vietnam, although the number of Green Building Certified projects has increased significantly since 2015, especially those with LEED certification. Certification adds value to the project but also incurs additional costs and implementation challenges for general contractors (GCs) and other stakeholders. The growing popularity of LEED buildings requires GCs to understand their ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 67 publications
2
21
0
Order By: Relevance
“…This means that more conflict of interest among stakeholders, more unforeseen circumstances, longer green construction practices, more alteration and variation during the construction process, more communications and collaboration among project team members and more complex construction documents and reports are significant challenges to general contractors in executing GB projects in Vietnam. This result is consistent with the previous studies' findings, such as Pham et al (2019), Hwang and Ng (2013), Li et al (2011). As mentioned, the Vietnam GBTs market lacks green construction materials/equipment; and such green products also often lack of necessary green performance certificates.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This means that more conflict of interest among stakeholders, more unforeseen circumstances, longer green construction practices, more alteration and variation during the construction process, more communications and collaboration among project team members and more complex construction documents and reports are significant challenges to general contractors in executing GB projects in Vietnam. This result is consistent with the previous studies' findings, such as Pham et al (2019), Hwang and Ng (2013), Li et al (2011). As mentioned, the Vietnam GBTs market lacks green construction materials/equipment; and such green products also often lack of necessary green performance certificates.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent strongly with the Table 7. Bootstrapping results of the structured model JED results of Pham et al (2019), Hwang et al (2015), Li et al (2011), and Robichaud and Anantatmula (2010). Pham et al (2019) showed that Vietnamese general contractors lack experience in selecting and documenting the purchasing of LEED materials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LEED protocol was introduced in 1993 aiming at minimizing environmental impacts of built environment starting from design phase up to its use and decommissioning, through energy/resources efficiency actions [15]. LEED plays a significant role among green building certification systems [16][17][18][19][20][21] and most of the green building projects are based on it [22].…”
Section: State Of the Artmentioning
confidence: 99%
“…By the end of 2019, over 146,400 projects had been registered with LEED [11]. By providing technical guides to help users balance environmental protection, energy performance, and financial benefits, LEED promotes these values in its building projects [1,2,12,13]. In addition, green building projects often gain additional financial support as a result of policies that create further advantages for developers working on green building projects [14].…”
Section: Introductionmentioning
confidence: 99%